Eratorpena Larramendiren hiztegian (I): eratorbideen analisia - Urgell, Blanca (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2003)
My main objective in this paper is to present the conclusions drawn from the study of morphological derivation in Larramendi’s Diccionario Trilingüe del Castellano, Bascuence y Latín (1745), based in a suffix-by-suffix analysis of the partial corpus employed (namely, Basque words beginning with (H)A) that will be published as the second part of the present work (Urgell 2004b). This work is a part of a larger research developed in my Ph.D. thesis (Urgell 2000a) on the Basque words compiled in the Diccionario Trilingüe, a dictionary famous because of its innovative side (i.e. a lot of neologisms, sometimes made in an odd, unknown or indecipherable way), but which remained unanalyzed until now. My approach focused on both searching Larramendi’s sources and revealing his methods of word-formation, with the aim of identifying as far as possible those which belong to tradition, and those which are really uncommon or new. As for derivation, I use Azkarate’s classification (1991) and her model of analysis. Thus, I analyze the distribution and selection of suffix allomorphs, the base forms of the derivatives and the meaning they acquire, the phonetic changes produced by derivation and the derivational chaines attested. On this basis, the productivity or fossilization of all these factors is evaluated, and the role of derivation in Larramendi’s dictionary is considered. This research reveals many aspects of the words collected in it, and also of Larramendi as a dictionary-maker and as a neologist, most of them completely unknown; it also makes advances in the understanding of the theoretical assumptions and analogical patterns which his innovations are based on.